Redesign of Hazardous and Toxic Waste Temporary Storage at PT ABC - Reni Dwi Septiani; Temmy Wikaningrum (Jurnal Serambi Engineering, 2023)
PT ABC is an industry that produces hazardous and toxic waste. All waste generated is stored in temporary storage, but based on observations made, the existing temporary storage does not meet the standards set by the government. Therefore, a temporary storage area was redesigned at PT ABC in accordance with the standards set by the government. The objective of this study is to find a temporary storage place that complies with government regulations for PT ABC. The method used is to record the types, characteristics, and quantities produced by PT ABC, followed by existing observation, then proceed with the calculation of facility requirements according to SNI and individual calculations. A redesign is carried out by adjusting the calculation results, determining the required facilities, and making a design proposal. The results showed that PT ABC requires temporary storage of 6,1 m x 2,6 m x 4,4 m to accommodate all the waste generated for 3 months with the number of drums needed, namely 5 drums. The total ventilation needed is 6 pieces with a size of 0.5 m x 0.5 m. The required size of the spill container is 2.2 m x 1.2 m x 0.6 m, and it takes 3 lamps to illuminate the temporary storage.